CLIC1 and CLIC4 ion channels as therapeutic targets for tumour treating fields in paediatric high grade glioma - Griffin, Michaela (2023)
Background: The lack of treatments for paediatric high-grade glioma represents one of the most significant unmet clinical needs in paediatric cancers. pHGGs form a subset of lethal brain tumours with a median overall survival of only 14 months; forming the leading cause of CNS cancer-related death in children. OptuneTM, a non-invasive electrotherapy device that delivers alternating electric fields – coined tumour treating fields (TTFields) – into the tumour. Despite success in adult trials, TTFields treatment is currently not approved in the paediatric population. Increasing evidence show that ion channels not only regulate electrical signalling of excitable cells, but also play a pivotal role in the development and progression of brain tumours. Membrane potential is a crucial biophysical signal that modulates the malignant processes via a plethora of tightly controlled ionic exchange processes. We aim to identify potential targets for TTFields and provide a proof-of-principle to elucidate the role of ion channels for multimodal therapies for paediatric high-grade gliomas.